2018
DOI: 10.1051/e3sconf/20186507007
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of SVR-Based Drought Forecasting Models using Wavelet Pre-Processing Technique

Abstract: Drought is a damaging natural hazard due to the lack of precipitation from the expected amount for a period of time. Mitigations are required to reduced its impact. Due to the difficulty in determining the onset and offset of droughts, accurate drought forecasting approaches are required for drought risk management. Given the growing use of machine learning in the field, Wavelet-Boosting Support Vector Regression (W-BS-SVR) was proposed for drought forecasting at Langat River Basin, Malaysia. Monthly rainfall,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The superior agreement between observed and predicted SPEI indicated the potential of the developed models for contributing more in understanding the potential future of drought-risks in eastern Australia. Fung, Huang, and Koo (2018) studied the improvement of SVR-based drought forecasting models using wavelet preprocessing techniques in the Langat River basin. Prediction of the SPEIs of hybrid wavelet models compared with SVR and the Boosted-support Vector Regression (BS-SVR) models showed that hybrid wavelet BS-SVR model provided more accuracy for the prediction of drought in the Langat River basin.…”
Section: Introductionmentioning
confidence: 99%
“…The superior agreement between observed and predicted SPEI indicated the potential of the developed models for contributing more in understanding the potential future of drought-risks in eastern Australia. Fung, Huang, and Koo (2018) studied the improvement of SVR-based drought forecasting models using wavelet preprocessing techniques in the Langat River basin. Prediction of the SPEIs of hybrid wavelet models compared with SVR and the Boosted-support Vector Regression (BS-SVR) models showed that hybrid wavelet BS-SVR model provided more accuracy for the prediction of drought in the Langat River basin.…”
Section: Introductionmentioning
confidence: 99%